On Ïˆgs-closed Sets in Bitopological Spaces (European Journal of Pure and Applied Mathematics, 2021)
In this paper, the properties of Ïˆgs-closed sets in bitopological spaces are investigated. The relationships between Ïˆgs-closed set and other closed sets in bitopological spaces are established and some properties of Ïˆgs-closure and Ïˆgs-interior are provided.
Keywords: Bitopological Spaces; psi gs-closed sets; psi gs-interior; psi gs-closure